The Interaction of Arbuscular Mycorrhizal Fungi and Phosphorus Inputs on Selenium Uptake by Alfalfa (Medicago sativa L.) and Selenium Fraction Transformation in Soil - Peng, Qi; Wu, Miaomiao; Zhang, Zekun; Su, Rui; He, Honghua; Zhang, Xingchang (Frontiers in Plant Science, 2020)
Selenium (Se) is a beneficial element to plants and an essential element to humans. Colonization by arbuscular mycorrhizal fungi (AMF) and supply of phosphorus (P) fertilizer may affect the bioavailability of Se in soils and the absorption of Se by plants. To investigate the interaction between AMF and P fertilizer on the transformation of soil Se fractions and the availability of Se in the rhizosphere of alfalfa, we conducted a pot experiment to grow alfalfa in a loessial soil with three P levels (0, 5, and 20 mg kg-1) and two mycorrhizal inoculation treatments (without mycorrhizal inoculation (-AMF) and with mycorrhizal inoculation (+AMF)), and the interaction between the two factors was estimated with two-way ANOVA. The soil in all pots was supplied with Se (Na2SeO3) at 1 mg kg-1. In our results, shoot Se concentration decreased, but plant Se content increased significantly as P level increased and had a significant positive correlation with AMF colonization rate. The amount of total carboxylates in the rhizosphere was strongly affected by AMF. The amounts of rhizosphere carboxylates and alkaline phosphatase activity in the +AMF and 0P treatments were significantly higher than those in other treatments. The concentration of exchangeable-Se in rhizosphere soil had a positive correlation with carboxylates. We speculated that rhizosphere carboxylates promoted the transformation of stable Se (iron oxide-bound Se) into available Se forms, i.e. exchangeable Se and soluble Se. Colonization by AMF and low P availability stimulated alfalfa roots to release more carboxylates and alkaline phosphatase. AMF and P fertilizer affected the transformation of soil Se fractions in the rhizosphere of alfalfa.